A Critical Theoretical Approach to Sport-Based Youth Development Research: Yosso’s Community Cultural Wealth Framework - Doo Jae Park; Wonjun Choi; Wonju Lee; NaRi Shin (Youth, 2025)
This paper proposes the application of Yosso’s Community Cultural Wealth (CCW) framework, rooted in the critical race theory (CRT), as a transformative lens for sport-based youth development (SBYD) research. Moving beyond traditional deficit-based models, which often depict youth as problematic or at-risk, CCW emphasizes recognizing and building upon the cultural strengths and assets of marginalized youth. We begin by reviewing the development of theoretical applications within the youth development, positive youth development (PYD), and SBYD literature to highlight the criticisms against conventional deficit-focused approaches. CCW offers an asset-oriented lens by offering six forms of capital—aspirational, linguistic, familial, social, navigational, and resistant—that are typically overlooked in mainstream frameworks. We illustrate how these forms of capital can reposition SBYD programs as spaces for cultivating resilience, identity, and social justice while addressing systemic inequities. By incorporating CCW with participatory research methods and critical theories, such as intersectionality and CRT, researchers can broaden the theoretical and methodological scope of SBYD. This paper concludes by suggesting practical implications for program design, organizational advocacy, and policy development, advocating for culturally responsive, community-led initiatives that prioritize the active engagement and empowerment of marginalized youth. In sum, CCW provides the “why” for critical SBYD research and practice.